Adenoid Basal Carcinoma of Cervix: A Rare Case Report (Nepalese Medical Journal, 2020)
Adenoid basal carcinoma of the uterine cervix is a rare low-grade tumor and its cell origin is still obscure. Adenoid basal carcinoma can be confused with adenoid basal hyperplasia, adenoid cystic carcinoma, and basaloid squamous cell carcinoma of the cervix. We present here a case of a 59 year-old-female who initially presented with a high-grade squamous intraepithelial lesion on Pap smear. Total abdominal hysterectomy with bilateral salpingo-oophorectomy was performed. Histopathology revealed focal invasive adenoid basal carcinoma with extensive areas of a high-grade squamous intraepithelial lesion involving the endocervical gland. The immunohistochemical stain was positive for p16.